Effects of the end-stop mechanism on the nonlinear dynamics and power generation of a point absorber in regular waves. (15th December 2021) - Chen, Mingsheng; Xiao, Panpan; Zhang, Zhibo; Sun, Liang; Li, Fen
Abstract: A hybrid frequency-time domain model is proposed to analyse the nonlinear dynamic responses and power generation of the point absorber with the end-stop system in regular waves. The hydrodynamic coefficients and wave excitation forces on the floater are obtained in the frequency-domain. A time-domain model is then established based on Cummins equation, in which the time-consuming convolution integral is replaced by more efficient state-space model. The PTO system and end-stop mechanism are modelled as linear spring-damper systems, which together behave like a trilinear-damper system constraining the motions of the floater under the wave excitations. The present model is cross-verified with ANSYS-AQWA and good agreement is achieved. Numerical results illustrate that appropriate stiffness of end-stop spring may improve the power generation efficiency in waves with long periods. In addition, the performance of the point absorber is found to be sensitive to the distance ratio that is the distance divided by the wave amplitude, and an optimal distance ratio is found to exist for the wave periods considered. The developed model may be potentially helpful in guiding the design of the end-stop systems for a given sea-states with prevailing wave periods. Highlights: An efficient numerical model with a self-adaptive integration method is developed for analysing the end-stop system. The developed model is verified with AQWA, which can identify high-order sub-harmonic motions. An optimal end-stop spring stiffness is found to exist for sea-states with longer wave periods. The performance of the point absorber is found to be sensitive to the gap ratio of the end-stop system. The developed model is useful in guiding the design of the end-stop system for a given prevailing sea-state.